Multiplexed bead-based assay for the simultaneous quantification of human serum IgG antibodies to tetanus, diphtheria, pertussis toxin, filamentous hemagglutinin, and pertactin - Rathod, Vishal; Kadam, Laxmikant; Gautam, Manish; Gumma, Prabhu Dasu; Marke, Kevin; Asokanathan, Cathy; Douglas-Bardsley, Alex; Hassell, Laura; Bhandare, Sachin; Gupta, Sumit; Parekh, Sameer; Pujari, Pramod; et al. (Frontiers in Immunology, 2023)
Background Luminex bead-based assays offer multiplexing to test antibodies against multiple antigens simultaneously; however, this requires validation using internationally certified reference standards. Therefore, there is an urgent need to characterize existing reference standards for the standardization of multiplex immunoassays (MIAs). Here, we report the development and validation of an MIA for the simultaneous estimation of levels of human serum immunoglobulin G (IgG) antibodies for pertussis toxin (PT), filamentous hemagglutinin (FHA), pertactin (PRN), diphtheria toxoid (DT), and tetanus toxoid (TT). Methods The MIA was assessed using a panel of human serum samples and WHO reference standards. The WHO reference standards were also studied for suitability in the MIA. Purified antigens (PT, FHA, PRN, DT, and TT) were coupled to the spectrally unique magnetic carboxylated microspheres. The method was validated in accordance with the United States Food and Drug Administration (US FDA), European Medicines Agency (EMA), and the International Committee of Harmonization Multidisciplinary (ICH M10) guidelines, and parameters such as precision, accuracy, dilutional linearity, assay range, robustness, and stability were assessed. Method agreements with commercially available IgG enzyme-linked immunosorbent assay (ELISA) assays were also evaluated. In addition, the study assessed the level of correlation between the IgG levels estimated by the MIA and the cell-based neutralizing antibody assays for PT and DT. Results We identified that an equimix of WHO international standards (i.e., 06/142, 10/262, and TE-3) afforded the best dynamic range for all the antigens in the MIA. For all five antigens, we observed that the back-fitted recoveries using the four-parameter logistic (4-PL) regression fits ranged between 80% and 120% for all calibration levels, and the percentage coefficient of variation (% CV) was < 20%. In addition, the difference in mean fluorescence intensity (MFI) between the monoplex and multiplex format was < 10% for each antigen, indicating no crosstalk among the beads. The MIA also showed good agreement with conventional and commercially available assays, and a positive correlation (> 0.75) with toxin neutralization assays for PT and DT was observed. Conclusion The MIA that was calibrated in accordance with WHO reference standards demonstrated increased sensitivity, reproducibility, and high throughput capabilities, allowing for the design of robust studies that evaluate both natural and vaccine-induced immunity.